Codes of Misconduct: The Regulation of Prostitution in Colonial Bombay - Jeffrey, Leslie Ann (Labour / Le Travail, 2011)
The article reviews the book, "Codes of Misconduct: The Regulation of Prostitution in Colonial Bombay," by Ashwini Tambe.
Keywords: BOOKS – Reviews; CODES of Misconduct: The Regulation of Prostitution in Colonial Bombay (Book); INDIA; Nonfiction; Prostitution; TAMBE; Ashwini